Time sharing performance of egocentric and allocentric frames of reference as an indicator of resource pool - Patton, Colleen E., author; Clegg, Benjamin, advisor; Wickens, Christopher, committee member; Ortega, Francisco, committee member (Colorado State University. Libraries, 2021)
The Multiple Resource Model (MRM) sets forth groups of cognitive resources and is used to predict dual task interference. Recent updates to the model suggest that it may not be all encompassing. The current studies aim to determine the resource use of egocentric and allocentric frames of reference (FoR) within the criteria of the MRM. Egocentric and allocentric FoR have been widely studied for their use in navigation aids, especially in aviation, and a plethora of neurological research has attempted to determine the neural correlates of each FoR. These two bodies of literature support the first two criteria of being considered separate resources, but the time sharing capabilities (the last criterion) have not been investigated. The current research used a dual task paradigm under intermediate and heavy resource use to determine how these FoR can be time shared. Results between experiments conflicted but indicated a stronger tendency toward improved performance under conditions in which the FoR being used for both tasks was the same. This was unexpected and does not fit into the MRM. Improved performance may be a result of task similarity, which can improve performance according to the shared processing routines hypothesis. Implications for navigation aid design are discussed.